Transformational Leadership and Creative Behavior Impact on Supply Chain Management: A Study of the Opinion of a Sample of Decision Makers in The Transportation, Distribution, And Materials Handling - D. Makkiyah Kraidi Bunyan Alkabi; D. Dunya Tarik Ahmed Salih Al-Qaisi (International Journal of Supply Chain Management, 2018)
Abstract - This paper examines the effect of managerial transformational leadership on supply chain organizational learning and supply chain correlation. We also assessed the impact of uncertainty in the working environment on these relationships. By integrating multiple perspectives on organizational behavior related to learning and leadership, we developed a research model and evaluated it using survey data. The results of this analysis support the concept that the direction of supply chain organization learning fully manages the relationship between transformational leadership and supply chain correlation. Also, uncertainty in the working environment positively manages the relationship between transformational leadership and supply chain learning. The purpose of this research is to determine the effect of transformational leadership in the creative behavior of decision makers in the supply chain management of Directorate of Public Traffic. The research problem was formulated in several questions focused on the statement of impact among its variables. The research was based on a main hypothesis, which was subjected to several tests to ascertain its validity. In order to achieve the objectives of the research, a questionnaire was developed which included (30) items to collect the data from the intentional sample of the research, with a total of (70) questionnaires, and the number of questionnaires valid for the analysis (67) of the total distributed questionnaires. The statistical program (SPSS) was used to analyze the data. The results are the most important: to drive the transformational leadership (ideal influence, inspirational motivation, intellectual arousal, individual legalism), which together have a significant effect on the creative behavior of the research sample members, and thus increase the attention to the positive strengths that form the transformational leadership contributes to the support and development of creative behavior of the organization, in question, to keep pace with progress in their field.